Iklan Sebagai Komunikasi Krisis Pandemi Covid-19 Dalam Promosi Pariwisata - Zakaria Lantang Sukirno; Tono Purwantoro (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2022)
Hotels and tourism industries have been affected by Covid-19 pandemic crisis in Indonesia since the end of March 2020. Hotel Santika and Amaris Hotels suffered that impact too, thus to overcome its crisis, they needed to apply a way of creative crisis communication using advertisement. How were the symbolization of crisis communication of Covid-19 pandemic on audio visual advertisements of Hotel Santika and Amaris Hotels? This research was held using Ferdinand de Saussure’s semiotics, applying creative visual analysis, and interview. The research unit of analysis were Hotel Santika and Amaris Hotels advertisements, and hotels customers as informants. The semiotics creative visual analysis showed those symbols of advertisements have described the health protocols. The interview results showed the hotels customers interpreted those advertisements could answer their anxiety, those became a persuasion for the public in new normal life, and those could provide them senses of secure, comfortable, and healthy at hotels.